Adaptation of time‐driven activity‐based costing to the evaluation of the efficiency of ambulatory care provided in the emergency department. Issue 4 (18th July 2022) - Berthelot, Simon; Mallet, Myriam; Blais, Sébastien; Moore, Lynne; Guertin, Jason R.; Boulet, Justine; Boilard, Christian; Fortier, Camille; Huard, Benoît; Mokhtari, Akram; Lesage, Annika; Lévesque, Émilie; et al.
Abstract: Objectives: The aim of this study was: (1) to adapt the time‐driven activity‐based costing (TDABC) method to emergency department (ED) ambulatory care; (2) to estimate the cost of care associated with frequently encountered ambulatory conditions; and (3) to compare costs calculated using estimated time and objectively measured time. Methods: TDABC was applied to a retrospective cohort of patients with upper respiratory tract infections, urinary tract infections, unspecified abdominal pain, lower back pain and limb lacerations who visited an ED in Québec City (Canada) during fiscal year 2015–2016. The calculated cost of care was the product of the time required to complete each care procedure and the cost per minute of each human resource or equipment involved. Costing based on durations estimated by care professionals were compared to those based on objective measurements in the field. Results: Overall, 220 care episodes were included and 3080 time measurements of 75 different processes were collected. Differences between costs calculated using estimated and measured times were statistically significant for all conditions except lower back pain and ranged from 4.30 to 55.20 (US) per episode. Differences were larger for conditions requiring more advanced procedures, such as imaging or the attention of ED professionals. Conclusions: The greater the use of advanced procedures or the involvement of ED professionals in the care, the greater is the discrepancy between estimated‐time‐based and measured‐time‐based costing. TDABC should be applied using objective measurement of the time per procedure.